Polychaetous annelids. Part VII. Capitellidae. - Hartman, Olga (Allan Hancock Pacific Expeditions, 1947)
[None. Introduction starts as follows:] This constitutes one of the oldest known groups of polychaetous annelids; it was already known in the late seventeen hundreds through the species Capitella capitata (Fabricius). The affinities of the group with other polychaetous annelids, however, were not clarified until detailed anatomical studies of organ systems had verified and proved their true relations. They had been variously considered as oligochaetes, representatives of Maldanidae, Arenicolidae, and Serpuliformia even as late as 1865 (see Eisig, 1887, pp. 1-10, for detailed history). The family name was first erected as the Capitellacea by Grube (1862) when Notomastus, Dasybranchus, and Capitella were correctly grouped together. A year later the family name, Halelminthea Carus, was proposed for Capitella, but this author considered it in the Oligochaeta together with an opheliid, Polyophthalmus; the name Halelminthea now has only historical interest. Today the various genera and species of Capitellidae (see below) are indisputably considered distinct, forming a closely related family; their affinities are with other sedentary chaetopods.
World Polychaeta Database (WPolyDb)